Respuesta :

Answer:

16x^3 - 6x  + 7/2

Step-by-step explanation:

32x^4 - 12x^2 + 7x by 2x

32x^4/2x =  16x^3

- 12x^2/2x = - 6x

 7x /2x = 7/2

So

32x^4 - 12x^2 + 7x by 2x =

16x^3 - 6x  + 7/2

For this case we must divide the following expressions:

[tex]32x ^ 4-12x ^ 2 + 7x[/tex] between [tex]2x[/tex]:

[tex]\frac {32x ^ 4-12x ^ 2 + 7x} {2x} =[/tex]

Separating terms:

[tex]\frac {32x ^ 4} {2x} - \frac {12x ^ 2} {2x} + \frac {7x} {2x} =[/tex]

We simplify:

[tex]16x ^ 3-6x + \frac {7} {2}[/tex]

Thus, [tex]\frac {32x ^ 4-12x ^ 2 + 7x} {2x} = 16x ^ 3-6x + \frac {7} {2}[/tex]

Answer:

[tex]16x ^ 3-6x + \frac {7} {2}[/tex]